Willingness to participate (WTP) in a future HIV vaccine trial in a high risk sample : perceived barriers and facilitators to participation - Parker, Fatima Bibi (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Psychology))--University of Stellenbosch, 2006.